Acheulean prepared core technologies from the eastern Zimbabwe Escarpment, Maunganidze (Manicaland). (August 2016) - Mercader, Julio; Patalano, Robert; Favreau, Julien; Itambu, Makarius; Kumbani, Joshua; Marufu, Happinos
Abstract: Evidence for an Early Stone Age occupation of the Zambezian zone prior to the late Acheulean is meager. In this article, we present an Acheulean site from eastern Zimbabwe called Maunganidze between the Limpopo and Zambezi, containing a wealth of large prepared cores, blanks, and large cutting tools that illustrate diversity and complexity in stone reduction. Acheulean hominins visited cobble-bed streams and outcrops as quarry sites leaving behind cores, blanks, hand axes, cleavers, and knives. The lithics studied were made on three main raw materials: quartzite, basalt, and rhyolite. Simple platform reduction and preferential prepared core technology dominate the assemblage. Blanks were obtained from large prepared cores. Three techniques for blank production were documented: side-struck prepared cores, sliced cobbles, and opening-flakes. The side struck assemblage shows significant preparation of the upper surfaces and a standardized approach for sub-triangular tabular supports, even highly symmetrical tear-drop blanks. The nearest comparative baseline comes from the South African Victoria West, documented 1300 km to the southwest. There are significant similarities and differences between the two sets. The site of Maunganidze represents the first Acheulean locus straddled along the transitional ecoregion that links southern, central, and east Africa. It is also the first time that the Victoria West industry has been documented outside South Africa's temperate zone, in the tropics. Highlights: Maunganidze is the first Acheulean locus straddled along the ecoregion that links southern, central, and east Africa. Gravelly cobble-bed streams adjacent to the moist foothills and good quality rock for knapping attracted hominins to this location. The nearest geographical comparative baseline comes from the South African Victoria West. Maunganidze is the first site containin Victoria West industries in the African tropics.